Endocrine Abnormalities and Growth Characterization in Colombian Pediatric Patients with 22q11 Deletion Syndrome - Juan Lasprilla Tovar; Nora Alejandra Zuluaga; Adriana Carolina Forero Torres; Oscar Correa-Jimenez; Javier Mauricio Sierra (Galenos Yayincilik, 2023)
INTRODUCTION: Several endocrine manifestations have been described in patients with 22q11 deletion syndrome, including growth retardation, hypoparathyroidism, and thyroid disorders. This study aimed to characterize these abnormalities in a Colombian retrospective cohort of children with this condition. METHODS: A retrospective study comprising a cohort of children with 22q11 deletion syndrome in Medellín, Colombia followed up between 2011 and 2017 was conducted. RESULTS: Thirty-seven patients with a confirmed diagnosis of 22q11 deletion syndrome were included. 37.8% had some endocrinopathy, the most frequent being hypoparathyroidism (21.6%), followed by hypothyroidism (13.5%), hyperthyroidism (2.7%) and growth hormone deficiency (2.7%). There was wide heterogeneity in the clinical presentation, with late onset of severe hypocalcemia associated with seizure or precipitated in postoperative cardiac surgery, which highlights the importance of continuous follow-up as indicated by the guidelines. Short stature was mainly related to nutritional factors. Growth monitoring is required with the use of syndrome-specific charts and careful monitoring of the growth rate. DISCUSSION AND CONCLUSION: As previously reported, a significant proportion of patients with endocrine abnormalities were found in this cohort. This highlights that it is essential to carry out an adequate multidisciplinary follow-up, based on the specific clinical guidelines, in order to avoid serious complications such as convulsions due to hypocalcemia. It is important to track size with curves specific to the syndrome and analyze the growth rate.